2018
DOI: 10.1002/ceat.201700476
|View full text |Cite
|
Sign up to set email alerts
|

Flue‐Gas Desulfurization by Using a HiGee Electric‐Field Device

Abstract: An innovative technique to remove SO2 from flue gas, comprising a rotating packed bed (RPB) coupled with an electric‐field device, is presented herein. The effects of operating conditions, such as packing type, rotation speed, gas‐liquid volumetric ratio, Na2SO3 content, and voltage supply on SO2 removal efficiency (η), as well as the gas‐phase overall volumetric mass‐transfer coefficient (KGa), were systematically investigated. Results indicate that a high η can be achieved under certain operating conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Regardless of the large proportion of CO 2 , the direct discharge of SO 2 from the waste gases into the atmosphere will pollute the atmosphere. Once SO 2 is involved in the water cycle of the atmosphere, the acid rain [2] will seriously damage the local ecological environment and cause immeasurable economic losses. Therefore, the national standards for atmospheric emissions are becoming strict, and enterprises are gradually adopting more efficient waste gas purification technology.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the large proportion of CO 2 , the direct discharge of SO 2 from the waste gases into the atmosphere will pollute the atmosphere. Once SO 2 is involved in the water cycle of the atmosphere, the acid rain [2] will seriously damage the local ecological environment and cause immeasurable economic losses. Therefore, the national standards for atmospheric emissions are becoming strict, and enterprises are gradually adopting more efficient waste gas purification technology.…”
Section: Introductionmentioning
confidence: 99%
“…In view of these, RPB has been successfully applied in distillation, absorption, bromination, wastewater treatment, etc. De-SO 2 by the WDFG method in RPB has been studied intensively and industrialized, showing special advantage in deep desulfurization. In our previous study, RPB has been adopted to absorb NO x with preoxidation by ozone into NaOH solution, and we found that RPB can accelerate the hydrolysis reactions of NO x which are controlling steps of the NO x removal process . However, these studies adopted a low gas–liquid ratio, and the NO x removal efficiency is relatively low.…”
Section: Introductionmentioning
confidence: 99%